Prevention of Ovarian Hyperstimulation Syndrome: A Review - Vinayak Smith; Tiki Osianlis; Beverley Vollenhoven (Hindawi Limited, 2015)
The following review aims to examine the available evidence to guide best practice in preventing ovarian hyperstimulation syndrome (OHSS). As it stands, there is no single method to completely prevent OHSS. There seems to be a benefit, however, in categorizing women based on their risk of OHSS and individualizing treatments to curtail their chances of developing the syndrome. At present, both Anti-Müllerian Hormone and the antral follicle count seem to be promising in this regard. Both available and upcoming therapies are also reviewed to give a broad perspective to clinicians with regard to management options. At present, we recommend the use of a "step-up" regimen for ovulation induction, adjunct metformin utilization, utilizing a GnRH agonist as an ovulation trigger, and cabergoline usage. A summary of recommendations is also made available for ease of clinical application. In addition, areas for potential research are also identified where relevant.